STATE YOUTH POLICY IN UZBEKISTAN: KEY STAGES AND OUTCOMES (International Congress on Economics, Management and Business Studies, 2026)
Youth represent the most important socio-demographic resource for the sustainable development of any state, and the design of an effective youth policy has become a strategic priority for modern public administration. In Uzbekistan, where young people constitute a large share of the population, the systematic development of legal, institutional, and programmatic mechanisms addressing education, employment, social protection, and civic engagement is of particular significance. This thesis presents the key findings of a broader study on the formation, development, and outcomes of state youth policy in the Republic of Uzbekistan.
Keywords: youth policy, Uzbekistan, New Uzbekistan strategy, youth institutions, digitalization, civic engagement.